Microfluidic plasma: Novel process intensification strategy - Lin Liangliang; Zhang Ziyi; Min Yuanping (Green Processing and Synthesis, 2022)
Microfluidic plasma is a novel process intensification strategy that integrates microfluidic and plasma together and uses their synergistic effects to provide new pathways for chemistry and chemical engineering. In this work, the unique properties and synergistic advantages of microfluidic plasma are introduced. According to the reactor configuration, three types of microfluidic plasmas are elaborated, including chip-based microfluidic plasma, tubular-based microfluidic plasma, and jet-based microfluidic plasma. Selected examples in nanofabrication, chemical synthesis, water treatment, etc., are provided to show their applications in diverse fields. Finally, the existing challenges of this technique have prospected.